Osteology of the Permian temnospondyl amphibian Glanochthon lellbachae and its relationships - R. R. Schoch (Fossil Record, 2021)
The early Permian Meisenheim Formation of the Saar–Nahe Basin (Germany) is famous for its richness in vertebrate fossils, among which the temnospondyls were present with microvores and fish-eating apex predators. The latter trophic guild was occupied exclusively by the genus Sclerocephalus in that basin within a long time interval up to M8, whereas in M9, a new taxon, Glanochthon lellbachae, appeared. This taxon is defined by (1) a preorbital region 1.8–2.0 times as long as the postorbital skull table, (2) dermal ornament with tall radial ridges, (3) a prefrontal anteriorly wider with straight lateral margin, (4) a squamosal posteriorly only half as wide as the quadratojugal, (5) phalanges of manus and pes long and gracile, (6) carpals unossified in adults, and (7) tail substantially longer than skull and trunk combined. Phylogenetic analysis finds that G. lellbachae forms the basal sister taxon of the stratigraphically younger G. angusta and G. latirostre and that this clade nests within the paraphyletic taxon Sclerocephalus, with S. nobilis forming the sister taxon of the genus Glanochthon (urn:lsid:zoobank.org:act:3038F794-17B9-4FCA-B241-CCC3F4423651; registration date: 15 March 2021).